2014
DOI: 10.1128/aac.01440-13
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Hydroxychloroquine in Lymphoid Tissue in a Rabbit Model for HIV Infection

Abstract: Hydroxychloroquine has been proposed for HIV treatment; however, little is known about its disposition in the lymphatic system, where replication takes place. Therefore, its distribution in lymphoid tissues (Peyer's patches and popliteal, submandibular, femoral, splenic, and prescapular lymph nodes) was evaluated and compared with that in blood. Results showed a high affinity of hydroxychloroquine for all of these tissues, with higher affinity for the splenic and submandibular lymph nodes, suggesting its poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…After taking these dosages, it was demonstrated that the mean HCQ concentration was significantly higher in At than in plasma [ 21 ]. This different drug distribution was also confirmed by an in vivo study using rabbits as an experimental model, receiving 15 mg/kg of HCQ subcutaneously [ 22 ]. Thus, the anti-HIV activity of HCQ could be linked to its accumulation in lymphoid tissue, a relevant site for HIV immunopathogenesis and replication.…”
Section: Resultsmentioning
confidence: 63%
“…After taking these dosages, it was demonstrated that the mean HCQ concentration was significantly higher in At than in plasma [ 21 ]. This different drug distribution was also confirmed by an in vivo study using rabbits as an experimental model, receiving 15 mg/kg of HCQ subcutaneously [ 22 ]. Thus, the anti-HIV activity of HCQ could be linked to its accumulation in lymphoid tissue, a relevant site for HIV immunopathogenesis and replication.…”
Section: Resultsmentioning
confidence: 63%
“…As a result, it is possible that the introduced N9 gel in the current study may contribute to the increased HCQ accumulation in the DC and PC portions of the rabbit vagina by absorbing the released HCQ and evenly spreading the cervicovaginal lumen. The use of a topical delivery system in the current study and the reported short half-life of HCQ in rabbit blood (10.6 hr) [28] may be some of the reasons that HCQ is undetectable in the blood.…”
Section: Discussionmentioning
confidence: 90%
“…100 µL of HCQ mobile phase was used to reconstitute the content in the vial and 80 µL was injected for HPLC analysis. HCQ in rabbit vaginal tissue or blood was first extracted and then analyzed by RP-HPLC using a modified extraction technique as previously reported [28]. Briefly, 500 ± 50 mg of rabbit vaginal tissue (UV, DC, and PC portions) were weighed in a 1.5 mL microcentrifuge tube with the addition of 400 µL of 3 mg/mL collagenase in water.…”
Section: Reversed-phase Hplc (Rp-hplc) Quantitation Of Hcq In Rabbit Cvl Tissue and In Implantsmentioning
confidence: 99%
“…CQ analogues have strong affinities to blood constituents and are highly protein-bound, particularly to thrombocytes and granulocytes, which reduces its plasma concentration. In addition, a major fraction of CQ analogues in plasma is bound to plasma proteins, primarily albumin [23][24][25] .…”
Section: Pharmacokinetic Properties Of Hydroxychloroquinementioning
confidence: 99%